Novel Simultaneous Decompression Through Single-stage Mini-thoracotomy for Concurrent Ossification of the Posterior Longitudinal Ligament and Ossification of the Ligamentum Flavum at the Same Thoracic Level: A Technical Report and Literature Review. Issue 3 (1st February 2021) - Yoon, Jongwon; Bae, Junseok; Shin, Sang-Ha; Bae, Youngsik; Lee, Sang-Ho
Abstract : Study Design: Technical case report. Objective: To describe a novel technique of decompression through single-stage mini-thoracotomy for removing concurrent ossification of the posterior longitudinal ligament (OPLL) and ossification of the ligamentum flavum (OLF) at the same thoracic level simultaneously. Summary of Background Data: Concurrent OPLL and OLF at the same thoracic level is not common. Because these conditions lead to severe thoracic myelopathy, however, they require surgical decompression. To date, several cases with concurrent OPLL and OLF at the same thoracic level and surgical methods to treat these conditions have been described. However, no consensus on the surgical methods for the treatment these conditions has been established and these surgical methods have been also reported to be linked with the incidence of complication like neurological deterioration and the requirement of bone grafting and instrumentation. Methods: Three consecutive patients who presented with thoracic myelopathy caused by concurrent OPLL and OLF at the same thoracic level were treated by our novel surgical technique of decompression through single-stage mini-thoracotomy. Results: Simultaneous complete removal of OPLL and OLF through single-stage mini-thoracotomy was performed successfully in the three patients. All patients' preoperative symptoms gradually improved during the follow-up period, and no additional complications were associated with removal of OLF through thoracotomy. And there was no kyphotic change or instability in the thoracic spine after more than a year of follow-up although both bone grafting and instrumentation were not performed. Conclusion: This novel surgical technique is considered to be able to be a safe and effective alternative to the conventional treatment of selective cases of thoracic myelopathy caused by concurrent OPLL and OLF at the same thoracic level. Level of Evidence: 4 Abstract : Concurrent OPLL and OLF at the same thoracic level leads to severe thoracic myelopathy. Thus, these conditions require surgical decompression. Our novel surgical technique of simultaneous decompression through single-stage mini-thoracotomy is considered to be able to be a safe and effective treatment option for these conditions.